Demand analysis with partially observed prices - Ian Crawford; Matthew Polisson (Institute for Fiscal Studies (IFS), 2015)
In empirical demand, industrial organization, and labor economics, prices are often unobserved or unobservable since they may only be recorded when an agent transacts. In the absence of any additional information, this partial observability of prices is known to lead to a number of identi?cation problems. However, in this paper, we show that theory-consistent demand analysis remains feasible in the presence of partially observed prices, and hence partially observed implied budget sets, even if we are agnostic about the nature of the missing prices. Our revealed preference approach is empirically meaningful and easy to implement. We illustrate using simple examples.
Keywords: D11; D12; 330; demand; missing prices; partial identification; revealed preference